2022
DOI: 10.3390/ijerph19084459
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Predictors of Psychological Distress for Healthcare Workers in a Major Saudi COVID-19 Center

Abstract: This study investigated the relationship between fear of COVID-19, previous exposure to COVID-19, perceived vulnerability to disease, sleep quality, and psychological distress among healthcare workers (HCWs) in Taif city in Saudi Arabia, which has a population of 702,000 people. A cross-sectional study design was adopted. HCWs (n = 202) completed a survey containing the Fear of COVID-19 Scale (FCV-19S), Perceived Vulnerability to Disease (PVD), Pittsburgh Sleep Quality Index (PSQI), and Depression, Anxiety, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…There were also significant associations between loss-of-confidence factors and experience level, hospital name, and a history of visiting psychological clinics. These findings correspond with those from previous studies [17,23,25,28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There were also significant associations between loss-of-confidence factors and experience level, hospital name, and a history of visiting psychological clinics. These findings correspond with those from previous studies [17,23,25,28].…”
Section: Discussionsupporting
confidence: 93%
“…Some previous studies have investigated psychological distress among physicians and nurses in Saudi Arabia; however, we believe that our study may be the first to assess levels of psychological well-being using the GHQ-12 instrument. Comparing our results with those from studies among physicians and nurses in Saudi Arabia that used different instruments revealed that the psychological distress levels in our study were higher than those in some studies [22,23], whereas they were similar to those in other studies [24,25]. Although physicians and male respondents reported higher scores for psychological distress than nurses and female respondents, these differences were not significant.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…HCPs were given the Italian version of validated questionnaires described thereinafter, which are also commonly used in HCP cohorts [ 18 , 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation of the study was that patient were not asked about previous history of anxiety, this could be correlated with anxiety level in the baseline level before COVID-19. However, other studied showed that there is no relation of previous exposing to infectious diseases and level of anxiety (48).…”
Section: Discussionmentioning
confidence: 92%